US-EU Trade Cooperation in the Context of Changing American Foreign Economic Policy - Yu. A. Konovalova; S. A. Ushanov; I. S. Zarubin (Vestnik MGIMO-Universiteta, 2020)
Abstract: The article examines changing dynamics and structure of US foreign trade with the EU countries, caused by the changes in US foreign trade policy after D. Trump came to power. The United States sets the general mood in the system of international economic relations, and in particular, in international trade. The strengthening of protectionism, the growth of disintegration processes (revision of the conditions of NAFTA / USMCA, US withdrawal from the TPP, stopping negotiations on the TTIP) is the response of Trump administration to the challenges faced by the United States. Globalization and liberalization have ceased to meet the interests of the American economy, which has led to a revision of the ideological foundations and practice of foreign economic activity.Statistics show that the United States' economic interest in the EU comes from the competitive advantages of individual EU countries. There is a possibility of continuing disintegration in the European Union, since after Brexit the Netherlands and other countries expressed the idea of leaving the Union. This will play into the hands of the United States, which is interested not in a strong united Europe, but in increasing the effectiveness of bilateral ties with individual countries of the European Union. The main conclusion of the study is the following: the globalization process and the interdependence of economies have weakened, and regardless of the results of the presidential elections, regardless of whether the United States will continue to pursue a policy of protectionism and conduct "trade wars", whether the crisis of 2020-2021 predicted by UNCTAD and IMF will come true, the EU and the US willbe forced to seek compromises and revise the conditions for reformatting the failed TTIP.